Restoration of Livestock Services in Conflict and Drought Affected areas of Ethiopia (RESTORE): Gender capacity development training report - Lemma, Mamusha; Berhe, Tsega; Knight-Jones, Theodore J.D. (International Livestock Research Institute, 2025)
This report presents the outputs of a gender capacity development training conducted for animal health and feed experts in the Restoration of Livestock Services in Conflict and Drought Affected Areas of Ethiopia (RESTORE) regions. The European Union (EU)-supported RESTORE project, which is implemented by the International Livestock Research Institute (ILRI) and the Ethiopian Veterinary Association (EVA) in the Afar, Tigray, and South Ethiopia regions, aims to enhance livestock sector resilience by addressing both conflict and drought-related crises. Integrating gender considerations is a central component of the project’s planning and implementation. Building on the gender mainstreaming strategy of the Health of Ethiopian Animals for Rural Development (HEARD) project, the RESTORE project identifies core gender integration activities to ensure gender issues are systematically analyzed and addressed in the project cycle. As a foundational activity, the project conducted gender capacity development training, which was designed in response to an online gender capacity assessment that identified gaps in knowledge, skills, and practical integration of gender-responsive approaches within livestock service delivery. Thirteen service providers (4 female) from RESTORE and previously HEARD-supported regions participated in the training held at ILRI, Ethiopia, from 30 June to 2 July 2025. The program employed experiential, reflective, and collaborative learning methodologies. Interactive activities such as case study analysis, role-plays, group discussions, and storytelling were central to deepening participants’ understanding of gender concepts and their application in animal health and feed services. Pre- and post-training knowledge assessments demonstrated measurable gains in participants’ understanding of gender integration. Additional tools, including mood meters, daily reflections, and feedback teams, supported continuous learning and adaptation. Participants reported greater confidence in integrating gender considerations into project planning, implementation, and evaluation. They valued the interactive and practical nature of the training and identified the need for continued support and local-level capacity building. This training represents a significant step toward more equitable, inclusive, and effective livestock service delivery, as it equips animal health and feed experts with the knowledge and tools necessary to address gender disparities in their work.